2015
DOI: 10.1128/jvi.01146-15
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of HIV-1 RNA Near the Plasma Membrane during Virus Assembly

Abstract: To increase our understanding of the events that lead to HIV-1 genome packaging, we examined the dynamics of viral RNA and Gag-RNA interactions near the plasma membrane by using total internal reflection fluorescence microscopy. We labeled HIV-1 RNA with a photoconvertible Eos protein via an RNA-binding protein that recognizes stem-loop sequences engineered into the viral genome. Near-UV light exposure causes an irreversible structural change in Eos and alters its emitted fluorescence from green to red. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…The dynamic interactions between HIV-1 Gag and RNA genome on plasma membrane have been described (29)(30)(31). We have previously studied the population dynamics of HIV-1 RNA on the plasma membrane and found that the presence of Gag protein significantly extends the time that HIV-1 RNA resides near the plasma membrane, indicating that most viral RNAs on the plasma membrane are in Gag-RNA complexes (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic interactions between HIV-1 Gag and RNA genome on plasma membrane have been described (29)(30)(31). We have previously studied the population dynamics of HIV-1 RNA on the plasma membrane and found that the presence of Gag protein significantly extends the time that HIV-1 RNA resides near the plasma membrane, indicating that most viral RNAs on the plasma membrane are in Gag-RNA complexes (31).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the population dynamics of HIV-1 RNA on the plasma membrane and found that the presence of Gag protein significantly extends the time that HIV-1 RNA resides near the plasma membrane, indicating that most viral RNAs on the plasma membrane are in Gag-RNA complexes (31). We have also examined HIV-1 RNA dimerization using live-cell total internal reflection fluorescence microscopy and observed that HIV-1 RNA molecules interact with each other dynamically on the plasma membrane, often when RNAs are associated with Gag signals.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that under native conditions, it is almost certain that Gag plays the dominant role in defining the preferred site of assembly by tethering gRNAs to the PM through the activity of its N-terminal matrix domain (13,40). However, we point out that our data do not rule out potential contributions from one or more cellular RNA binding proteins in addition to Gag that, like the MS2 targeting proteins, may modulate transient Gag/gRNA interactions with membranes or other cellular machineries.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also shed light on the time frame in which RNA dimerization occurs during virus assembly. In the presence of sufficient Gag proteins for virus assembly, it is likely that most HIV-1 RNAs are associated with some Gag proteins, because the overall dynamics of the viral RNA is altered (25). Thus, the RNA dimerization process is likely to be the merging of two Gag-RNA complexes, regardless of whether the Gag signal is detected.…”
Section: /Mkatementioning
confidence: 99%